Evaluation and comparison of microstructural and mechanical properties between carbon steel and microalloyed steel for railway wheel application - Oliveira, Luiz Gustavo de; Fukugauchi, Cristina Sayuri; Faria Neto, Antonio dos Reis de [UNESP]; Guimaraes, Valdir Alves [UNESP] (Univ Fed Rio De Janeiro, Lab Hidrogenio, 2020)
The railway sector has always been looking for an increase in the yield of its products involved in the transportation of cargo and passengers. One of the ways to increase the efficiency of this type of transport is based on increasing the speed of the trains and the loads transported per axle, which makes the railways more competitive. However, these solutions generate high stresses on the railway wheels, thus increasing the possibility of failure due to fatigue in them. In this context, the objective of this work is to evaluate the mechanical properties, including fatigue, and the microstructural characteristics of the materials used in the manufacture of railway wheels. Three different materials were evaluated (Carbon steel - cast and forged sample; Microalloyed steel - Forged sample) used in this segment through microstructural testing, traction, fracture toughness and fatigue, a wheel manufactured by forging and with class steel. C (0.7% C), one manufactured by casting with the same material and another forged wheel produced with vacuum-degassed class C steel and micro bonded with niobium and molybdenum. The results of the tests indicate that the forged and microalloyed wheel presented superior values of the mechanical properties when compared to the other studied materials. In addition, the forging manufacturing process showed better results when compared to the casting process.
Keywords: Micro Alloy Steel; Forging; Foundry; Fatigue; Fracture toughness